2022
DOI: 10.36456/farmasis.v3i1.5396
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review: Pengaruh Jahe (Zingiber Officianale) Terhadap Penurunan Frekuensi Mual Muntah pada Ibu Hamil

Abstract: Nausea and vomiting of pregnancy (NVP) adalah kecenderungan untuk memuntahkan sesuatu, atau sensasi yang muncul di kerongkongan atau epigastrium, dengan atau tanpa muntah. Hal ini dapat terjadi pada empat minggu pertama hingga pada minggu kedua belas kehamilan. Penatalaksanaan mual muntah selama kehamilan dapat dilakukan dengan terapi farmakologis dan non farmakologis, namun 34% wanita tidak mengkonsumsi obat dan 26% diantaranya mengurangi dosis karena kekhawatiran efek samping obat yang digunakan pada kehamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…An increase in estrogen can provoke an increase in stomach acidity that makes the mother feel nauseous. (Nurmi, 2018) (Austin, 2019) (Hariadini, 2022) Another theory says that placental cells (Villi kariolis) attached to the uterine wall is initially rejected by the body because it is considered a foreign body. This immunological reaction is what triggers the nausea reaction.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in estrogen can provoke an increase in stomach acidity that makes the mother feel nauseous. (Nurmi, 2018) (Austin, 2019) (Hariadini, 2022) Another theory says that placental cells (Villi kariolis) attached to the uterine wall is initially rejected by the body because it is considered a foreign body. This immunological reaction is what triggers the nausea reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Gingerol dan shogaols masuk ke dalam komponen utama yang aktif dalam farmakologi yang terkandung didalam Jahe. Jahe dapat mengurangi mual muntah dengan cara meningkatkan tonus dan motilitas lambung melalui aktivitas antikolinergik dan antiserotonergik serta dapat meningkatkan pengosongan lambung (Ebtavanny et al, 2022). Minyak atsiri yang terdapat didalam Jahe dapat mereleksasikan dan memblokir refleks muntah, sementara gingerol dan shogaol bisa meningkatkan sirkulasi darah dan saraf bekerja dengan baik dan memiliki anti mual, anti muntah.…”
Section: Jahe Dan Ondansetronunclassified
“…Prior to the intervention, the patient experienced nausea and vomiting an average of 13 times, and after the intervention, nausea and vomiting in patients could be reduced by up to 3.18 times (Rufaridah et al, 2019). Giving ginger 1-3 times a day for 4-30 days effectively reduced the frequency of nausea and vomiting and the severity of nausea and vomiting in pregnant women (Ebtavanny et al, 2022). Research by Abdolhosseini et al (2017) in the groups of pomegranate and spearmint syrup plus vitamin B6 showed the PUQE-24 score and the visual analog scale (VAS) scores were significantly lower than alone vitamin B6 on day 7.…”
Section: Introductionmentioning
confidence: 98%